2018
DOI: 10.1111/bju.14505
|View full text |Cite
|
Sign up to set email alerts
|

Immediate versus delayed exercise in men initiating androgen deprivation: effects on bone density and soft tissue composition

Abstract: Objectives To examine whether it is more efficacious to commence exercise medicine in men with prostate cancer at the onset of androgen‐deprivation therapy (ADT) rather than later on during treatment to preserve bone and soft‐tissue composition, as ADT results in adverse effects including: reduced bone mineral density ( BMD ), loss of muscle mass, and increased fat mass (FM). Patients and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
120
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(131 citation statements)
references
References 48 publications
7
120
1
Order By: Relevance
“…However, the lack of a control group precludes drawing firm conclusions. Studies that combined resistance with impact training demonstrated a preserved spinal [13][14][15] and femoral [15] BMD in men on ADT. Indeed, mechanical loading induced by resistance and impact training appears to be a precipitating factor in upregulating osteoblastic activity.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…However, the lack of a control group precludes drawing firm conclusions. Studies that combined resistance with impact training demonstrated a preserved spinal [13][14][15] and femoral [15] BMD in men on ADT. Indeed, mechanical loading induced by resistance and impact training appears to be a precipitating factor in upregulating osteoblastic activity.…”
Section: Discussionmentioning
confidence: 94%
“…The heterogeneity in terms of the duration of ADT exposure is another important limitation. Previous research has shown that initiating exercise early on ADT preserves BMD at lumbar spine, skeletal muscle mass, and density [14]. BMD was assessed at twelve months (six months after the intervention) according to the standard of care for men on ADT in Canada [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taaffe et al. in this issue of the BJUI discuss the value of exercise medicine – Immediate vs delayed exercise in men initiating androgen deprivation: effects on bone density and soft tissue composition.…”
mentioning
confidence: 99%